Combined image interpretation of computed tomography and hybrid PET in head and neck cancer - Zimny, M.; Wildberger, J. E.; Cremerius, U.; DiMartino, E.; Jaenicke, S.; Nowak, B.; Büll, U. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: Evaluation of potential synergistic effects of combined image interpretation of FDG PET using a gamma camera modified for coincidence detection (hybrid PET) and computed tomography (CT) and comparison of the diagnostic accuracy of hybrid PET and dedicated PET in patients with head and neck cancer. Methods: Forty-two patients with suspected primary or recurrent cancer were included. Twenty-four patients underwent dedicated PET in addition to attenuationcorrected hybrid PET using a one-day protocol. Results: Sensitivity, specificity and accuracy for detection of primary or recurrent head and neck cancer were 74, 73, and 74% for hybrid PET, 52, 82, and 60% for CT and 77, 82, and 79% for combined reading. With the combination of CT and hybrid PET all cases of recurrent disease were detected. The largest tumour not detected was 1.7 cm in diameter. Sensitivity, specificity and accuracy for the detection of neck sides with lymph node metastases were 69, 88, and 85% for hybrid PET, 62, 88, and 84% for CT, 69, 99, and 94% for combined image interpretation. With combined interpretation four involved neck sides were missed including two cases of microscopic metastases. Hybrid PET revealed concordant results to dedicated PET in all patients with respect to the detection of primary or recurrent tumour and in 45 of 48 neck sides (94%) with the same number of false negative findings. Conclusion: The combination of functional information of hybrid PET and morphological information of CT by the simple approach of combined image interpretation improves the sensitivity for the detection of primary/recurrent head and neck cancer and increases the specificity of lymph node staging compared to CT alone. The accuracy of hybrid PET and dedicated PET was almost identical.
Keywords: Head and neck tumours; fluorodeoxyglucose; hybrid PET; CT